Safar Bathing Ritual In Tanjung Punak Village Rupat District, Bengkalis Regency Riau Province - Umi Fariha; Ismail Pane (Rumah Riset Publisher, 2023)
This study aims to display the traditions of the local Islamic community known as the bathing safar ritual which gets the focus of various communications on islam itself. The safar bathing ritual is one of the legacies of the ancestors which is considered as a way of rejecting misfortune that will occur (accidents, disasters and epidemics). However, in local traditions that are directly related to islam, which generate pros and cons among the people who support and also reject this tradition. In connection with this reason, this research aims to find out the meaning of the symbol and function of this safar bath fot the people who support it. How far do they understand these rituals and skills for their daily lives and the role of the local government in maintaining these traditions.